Recent Advances in the Use of the Dimerization Strategy as a Means to Increase the Biological Potential of Natural or Synthetic Molecules - Paquin, Alexis; Reyes-Moreno, Carlos; Bérubé, Gervais (Molecules (Basel, Switzerland), 2021)
The design of C2-symmetric biologically active molecules is a subject of interest to the scientific community. It provides the possibility of discovering medicine with higher biological potential than the parent drugs. Such molecules are generally produced by classic chemistry, considering the shortness of reaction sequence and the efficacy for each step. This review describes and analyzes recent advances in the field and emphasizes selected C2-symmetric molecules (or axial symmetric molecules) made during the last 10 years. However, the description of the dimers is contextualized by prior work allowing its development, and they are categorized by their structure and/or by their properties. Hence, this review presents dimers composed of steroids, sugars, and nucleosides; known and synthetic anticancer agents; polyphenol compounds; terpenes, known and synthetic antibacterial agents; and natural products. A special focus on the anticancer potential of the dimers transpires throughout the review, notwithstanding their structure and/or primary biological properties.